WVREA heuristics : A comprehensive framework for evaluating usability in wearable virtual reality educational applications (WVREA) - Mohd Kamal, Othman; Rahimah, Mat; Norehan, Zulkiply (Springer Science+Business Media, LLC, 2025)
This research addresses the critical need for robust usability evaluation tools in Wearable Virtual Reality Educational Applications. We developed a comprehensive set of Wearable Virtual Reality Educational Applications usability heuristics through a multi-stage process. Initial heuristics were established through a literature review. Validation occurred in three phases, frst with academics and industry practitioners (n=25), second with experts in academics and industry (n=15), and third with end-user schoolteachers (n=15) and fnally, refnement based on feedback from all phases. Expert validation surveys refned the heuristics based on feedback regarding utility, clarity, ease of use, and the need for additional checklists. The revised heuristics received positive feedback from experts in human–computer interaction and virtual reality, as well as school teachers, indicating their efectiveness in addressing usability issues. This research establishes a foundation for standardised WVREA usability practices, providing a valuable tool for the WVREA development community. Future exploration could involve longitudinal studies and developing additional user interface-focused heuristics.